Beam Steering Antenna Array based on Reconfigurable Feeding Network - Singh A.; Jatav R.; Ajitesh; Meshram M.K. (My University, 2025)
This paper presents the design of a wideband pattern reconfigurable antenna array using a reconfigurable feeding network. The proposed antenna consists of three stacked dielectric substrates. Two rectangular parasitic patches are arranged on the top layer of the third substrate to widen the antenna bandwidth. To achieve the reconfigurability in radiation pattern, a reconfigurable feeding network is designed and arranged on the bottom layer of substrate 1. By turning the states of the pin diodes, the different excitation paths can be selected to steer the radiation pattern. The proposed antenna can steer its beam discretely from -36 deg. to +36 deg. with respect to the antenna broadside within the overlapping bandwidth from 4.6 GHz to 5.6 GHz. © 2022 IEEE.